Antibacterial and DPPH free radical-scavenging activities of methanolic extracts of Aaptos sp. (Marine Sponges) - Mohamad, Habsah; Mat Rashid, Zalilawati; Shaari, Khozirah; Latip, Jalifah; Lajis, Md Nordin; Ali, Abdul Manaf (Universiti Putra Malaysia Press, 2009)
This study reports on the evaluation of the antioxidant and antibacterial activities of twelve methanolic extracts (A-L) of Aaptos sp., collected from various locations of Terengganu Islands, namely Pulau Bidong, Pulau Kapas, Pulau Perhentian and Pulau Redang. The antioxidant activity of the twelve specimens was evaluated using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging method. The antibacterial bioassay against 5 bacteria, i.e. Bacillus subtilis (gram-positive), Escherichia coli (gram-negative), Bacillus proteus, Streptococus agalatea and Streptococus fecalis, was carried out using the disc-diffusion method. In the DPPH method, all extracts exhibited moderate and strong radical scavenging activity when compared to the standards used, i.e. quercetin and butylated hydroxyanisole (BHA) with the inhibition percentage in the range of 55â€“89%. In particular, specimen H exhibited the strongest radical scavenging activity with IC50 value of 0.1mg/ml. On the contrary, all the specimens showed antibacterial activity at least against one test organism. Interestingly, specimens C, G and L, which were collected from Perhentian, Bidong and Kapas Islands respectively, exhibited weak to strong activity against all bacterial strains. Beside that, specimen F (collected off Redang Island) was weakly bactericidal only against Bacillus proteus. Meanwhile, specimen G (collected off Bidong island) was primarily selected for further isolation to yield cholestan-3β-ol and aaptamine.